Antitubercular activity of the fungus gliocladium sp. MR41 strain - (:unkn) unknown (Iranian Journal of Pharmaceutical Research, 2019)
Tuberculosis (TB) is a leading cause of death worldwide from infectious diseases and its inadequate treatment has led to emergence of resistant strains. The emergence of these strains renders the search for new drugs for the treatment of TB. The aim of this study was the evaluation of the anti-TB activity of the extract from fungus Gliocladium sp. MR41, and bioassay-guided fractionation and identification of majority compounds was carried out. Fungal strain culture was lyophilized and extracted by maceration in Ethyl Acetate (EtOAc). This extract was fractionated by liquid-liquid partitioning and chromatographic techniques, and the compounds were identified by their spectroscopic data. Furthermore, the EtOAc extract, fractions, and pure compounds were tested on Mycobacterium tuberculosis using the Microplate Alamar Blue Assay. From the bioactive AcetoNitrile Fraction (AcNF; MIC = 3.13 µg/mL) of the EtOAc extract, four compounds were isolated: ergosterol (1), ergosterol-5, 8-peroxide (2), 1, 6-di-O-acetyl-2,3,4,5-tetrahydroxy-hexane (3), and allitol (4). Only 2 exhibited potent activities against M. tuberculosis (MIC = 0.78 µg/mL). Additionally, this is the first report, to our knowledge, of polyols 3 and 4 from this fungus. © 2019, Iranian Journal of Pharmaceutical Research. All rights reserved.
Keywords: Allitol; Antituberculosis activity; Ergosterol-5,8-peroxide; Gliocladium; Mycobacterium tuberculosis